2011
DOI: 10.1016/j.bbamcr.2010.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of dynamin II at serine-764 is associated with cytokinesis

Abstract: Calcineurin is a phosphatase that is activated at the last known stage of mitosis, abscission. Among its many substrates, it dephosphorylates dynamin II during cytokinesis at the midbody of dividing cells. However, dynamin II has several cellular roles including clathrin-mediated endocytosis, centrosome cohesion and cytokinesis. It is not known whether dynamin II phosphorylation plays a role in any of these functions nor have the phosphosites involved in cytokinesis been directly identified. We now report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…We show that these proteins localise to the FMRs and MR within the ICB. We have recently shown that dynII locates to the FMRs (Chircop et al, 2010) and functions here in an endocytic-independent manner for abscission (Chircop et al, 2011b). Numerous proteins that locate to the MR are involved in protein and vesicular recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…We show that these proteins localise to the FMRs and MR within the ICB. We have recently shown that dynII locates to the FMRs (Chircop et al, 2010) and functions here in an endocytic-independent manner for abscission (Chircop et al, 2011b). Numerous proteins that locate to the MR are involved in protein and vesicular recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…We next assessed whether IQGAP1 is involved in regulating recruitment and localization of key ICB components: g-tubulin (a MR component), 53 aurora B (presence and dephosphorylation at the ICB promotes abscission), 16 calmodulin (CaM -protects aurora B from being ubiquitinated), 54 calcineurin (CaNdephosphorylates proteins such as dynamin II prior to abscission), 55,56 and PRC1 (required for microtubule polarization as well as protein recruitment to the ICB). 57 Of these, CaM directly binds IQGAP1.…”
Section: Depletion Of Iqgap1 Does Not Disrupt the Contractile Ring Lomentioning
confidence: 99%
“…56,90 IQGAP1 gel bands, each containing immunopurified protein, were excised from colloidal Coommassie Blue-stained SDS gels. The bands were destained in 3 washes of 50 mM ammonium bicarbonate in a 50% (v/v) acetonitrile solution for 15 min at 37 C. Destained bands were then dehydrated with 100% acetonitrile solution for 15 min.…”
Section: Immunoprecipitation Of Iqgap1mentioning
confidence: 99%
“…Thus, an understanding of the molecular pathways that drive mitotic exit may highlight molecular targets for the development of new anti-cancer chemotherapeutic agents. In line with this idea, a recent publication has identified the CaN substrate, dynII, as a molecular target for the treatment of cancer (Chircop et al, 2010a, Chircop et al, 2010b. Inhibitors of dynII possess anti-cancer properties due to their ability to cause cytokinesis failure and subsequent cell growth arrest or apoptotic cell death (Joshi et al, 2010).…”
Section: Resultsmentioning
confidence: 85%
“…During cytokinesis CaN locates to two 1.1 m diameter flanking midbody rings (FMRs) that reside on either side of the 1.6 m diametertubulin midbody ring (MR) within the centre of the intracellular bridge. The endocytic protein, dynamin II (dynII), is mitotically phosphorylated by Cdk1/cyclin B1 upon mitotic entry and co-localises with CaN at the FMRs during cytokinesis (Chircop et al, 2010a, Chircop et al, 2010b. CaN inhibition by CsA, dynII depletion, phospho-mimetic dynII phosphopeptides and small molecule dynamin inhibitors lead to aborted cytokinesis and multinucleation (Joshi et al, 2010, Chircop et al, 2010a, Chircop et al, 2010b, Chircop et al, 2011.…”
Section: Can (Pp2b)mentioning
confidence: 99%